11 Carcass Attributes and Performance of Poultry (Gallus gallus domesticus) fed Olive Pomace. (28th November 2020) - Conn, Benny J; Snokhous, Payton; Carter, Ethan; Urso, Phil; Legako, Jerrad F; Kelley, Stanley F; Beverly, Marcy M; Anderson, Mark
Abstract: In livestock production systems, feed is the most expensive production input. The goal of any producer is to find feed that provides a balance of nutrients to meet requirements for maintenance, growth, and performance while efficiently contributing favorable carcass attributes at a low cost. Olive pomace, a by-product of the olive industry, can serve as a source of fat (14%), protein (3.6%), and fiber (44.5%). The objective of this study was to determine adipose tissue content and sensory attributes of chicken breast (Phase I), as well as determine growth of growing chickens fed a mixture of commercial feed and olive pomace (Phase II). In Phase I, mature broilers were fed rations consisting of 25%, 50%, and 75% olive pomace blended with standard poultry feed for 27d. After harvest, a fat sample was taken for fatty acid analysis, and a breast was taken from each bird for sensory analysis. The only difference in fatty acid composition was in the 50% treatment, which had lower amounts of docosahexaenoic acid and higher amounts of decanoic acid. No significant differences were detected between treatment groups in the sensory analysis (P = 0.79). The young chickens (n = 40) were divided into three groups and fed a standard diet (control), or a standard diet with either 25% or 75% replaced with olive pomace. They were fed ad libitum for 35d; total feed consumed was measured daily and bodyweight (BW) was recorded weekly. No difference was detected between control and 25% in BW, but the 75% was lighter (P < 0.01) than the other groups. Additionally, 75% consumed more feed (0.91/lb/bird/d; P < 0.01) than any other group with no difference between control (0.64/lb/bird/d) and 25% (0.71/lb/bird/d). The results show that olive pomace can be utilized in chicken rations and will not affect growth or the quality of the end product.